การพัฒนาผลสัมฤทธิ์ทางการเรียนวิชาการงานอาชีพและเทคโนโลยี ของนักเรียน ชั้นประถมศึกษาปีที่ 3 โรงเรียนวัดจินดาราม โดยใช้บทเรียนการ์ตูนมัลติมีเดีย ร่วมกับการจัดการเรียนรู้ด้วยเทคนิคโต๊ะกลม - ใจดี, มนัสนิต; สิงหาทอ, ปนิศรา (วารสาร ศึกษาศาสตร์ มมร, 2020)
The purposes of this research were 1) to develop the multimedia cartoon lesson on occupation and technology subjects based on the efficiency criteria 80/80, 2) to compare the learning achievement of the student before and after studied with the multimedia cartoon lesson cooperated with round table technique, and 3) to find the satisfaction of the students on studied with the multimedia cartoon lesson cooperated with round table technique. The sample group of this research was 30 students in grade 3 students of Wat Chindaram School by the simple random sampling of the classroom unit-based sampling. The research tools consisted of the lesson plan, multimedia cartoon lesson, achievement test, cartoon lesson’s quality evaluation form in content and technical and methodology, and students’ satisfaction questionnaire. Mean, percentage, standard deviation, and dependent t-test used in this research.           The research findings showed that 1) the multimedia cartoon lesson included 3 chapters; basic computer equipment, computer maintenance, and information technology benefits. The multimedia cartoon lesson had a quality of content and technique and methodology at the highest level. The effectiveness of the multimedia cartoon lesson was 87.44/86.11 which higher than the criteria 80/80, 2) the average of a post-test score was higher than pre-test score at a significance level of .05, and 3) the student satisfied with the multimedia cartoon lesson and studied with round table technique was at the highest level.